Instilling Social Values in Islamic Religious Education Learning in Junior High Schools - Zahra, Ildira Az; Rahmat, Munawar; Hermawan, Wawan; Syahrijar, Iqbal (Journal of Insan Mulia Education, 2024)
The phenomenon of religious and social values ​​of individuals and society is now increasingly dimming. This has implications for students' social character, where moral or ethical values ​​are ignored, egoistic, and a diminished sense of empathy for others. This research aims to determine the instillation of social values ​​in Islamic Education learning at SMPN 15 Bandung. This research method uses a descriptive qualitative approach to describe in detail the problems studied. The data collected came from primary data through observation, interviews and documentation at SMPN 15 Bandung. The results of the research show that instilling social values ​​in Islamic Education learning can be done through three social programs, including: 1) compensation program, in instilling these social values, Islamic Education teachers do not only focus on learning in the classroom, but Islamic Education teachers provide a good role model for students by providing donations to students who experience disaster. 2) Friday blessing program, this program has made students aware of the importance of sharing and being useful for others, in order to form students' characters who have social awareness and sympathy for others by providing good role models through sharing food every Friday. 3) 5S program, teachers are required to be good role models for students in the process of familiarizing themselves with 5S (Salam, Senyum, Sapa, Sopan, Santun), both in the school environment and outside the school environment. This research has implications for the importance of Islamic Education learning in instilling social values ​​in schools.